10 - The nexus of decision making, re-allocation and migration on Children orphaned and affected by HIV and AIDS: a case study of rural Lesotho - Hapazari, Josphine (African Sociological Review, 2022)
AIDS has become a calamity in Africa impacting on all various groups. It presents a myriad of challenges among which is the re-allocation of children orphaned by the disease, which is the focus of this study. The study investigates the re-allocation of children orphaned and affected by HIV and AIDS with the aim of establishing how migration decisions were arrived at and the socio-economic experiences of these children. Informed by the bounded rationality theory, it employed the qualitative approach to collect data on 30 orphaned children and from 12 care givers in six villages of Leribe district, in Lesotho. The study shows that decisions resided with adult family members and the re-allocation and relocation of children affected them socially, economically and psychologically. It concludes with the suggestion that further research is needed in this complex nexus of decision-making, re-allocation and migration of children orphaned by HIV/AIDS to aid policies and interventions by the government.